Cybersecurity threats to Healthcare Sectors during Covid-19 - Alghamdi, Abdulrahman (2022 2nd International Conference on Computing and Information Technology (ICCIT), 2022)
This paper has discussed cybersecurity threats and their mitigation of measures to be taken in the healthcare sector. Due to the corona pandemic, the cases of cybersecurity hiked up, bringing havoc to online operators. As many governments were busy combating the pandemic, cybercriminals took advantage primarily to attack healthcare systems globally. Furthermore, the healthcare sector has been prone to attacks due to its vulnerability. It has faced challenges in keeping patient's data confidential, thus making its ng its accessibility easy by attackers. As a result, this paper has highlighted the appropriate measures to be taken by the health care sector in terms of hospital system infrastructures and safety. The paper has also discussed the common cybersecurity threats to the health sector via diverse methodologies as studied in the literature review of this paper.